Nanotechnology enters the realm of superconductors.
EU-funded researchers succeeded in substantially increasing the current that thin, high-temperature superconductor films can conduct without loss in lengths suitable for commercial use. Results can change the way energy is produced and transmitted, enabling for example lossless power grids or motors and generators, and can produce extremely powerful magnets.